Simulasi Sistem Pentanahan Dengan Memodifikasi Konsentrasi Kadar Garam - Muhammad Taqiyyudin Alawiy (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2020)
Grounding system takes a very important role in the electricity and electronics device  protection system. The system is used for releasing current disturbance to the ground method. The smaller value of grounding system will give better system. In the certain ground, grounding resistance value is influenced by the depth and distance within the electrodes. The goal of this research is to find the characteristic of rod electrode grounding resistance and design computation method to calculate rod electrode resistance by changing its values and finally it can be used for the protection devices system reference. This research uses three point method to inject AC current into the electrode under test and a current probe and will give a potential between the earth electrode and the potential electrode, so the value of grounding resistance can be found. The result of the analysis indicates that the value of grounding resistance will be smaller when the deep of the planting, the amount of the rod electrode  buried and the distance of it are added. The decrease of grounding resistance value will be effective to 75 cm in deep and 300 cm in distance. While planting of rod electrode is deeper more than 75 cm and more 300 cm in distance not effective, because it can reduce the value of grounding resistance which does not have any mean. Therefore,  to get the small value of grounding resistance effectively, it is advised to add the amount of the electrode which is planted parallely. With the rod electrode installed before. However, it is important to notice when making the grounding system is the resistivity value of small and great of the ground  where the stability of grounding resistance is mounted. Finally, in planting grounding electrode it is important to have the geology data of the ground where the system applied.